2006
DOI: 10.1080/13803390500409583
|View full text |Cite
|
Sign up to set email alerts
|

Memory Evaluation in Mild Cognitive Impairment using Recall and Recognition Tests

Abstract: Amnestic mild cognitive impairment (MCI) is a selective episodic memory deficit that often indicates early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 52 publications
8
50
1
2
Order By: Relevance
“…Along these same lines, it is possible that memory deficits in MCI are still different from those in Alzheimer's disease. For example, recent research has suggested that some patients with MCI demonstrate relatively better performance on recognition trials than recall trials (Bennett et al, 2006;Westerberg et al, 2006), and better recognition memory might facilitate the expression of practice effects. Lastly, from both a methodological and conceptual standpoint, amnestic MCI is typically viewed as a heterogeneous group, comprised of patients who will progress to dementia and those who will remain stable for several years or even revert back to normal cognition (Winblad et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Along these same lines, it is possible that memory deficits in MCI are still different from those in Alzheimer's disease. For example, recent research has suggested that some patients with MCI demonstrate relatively better performance on recognition trials than recall trials (Bennett et al, 2006;Westerberg et al, 2006), and better recognition memory might facilitate the expression of practice effects. Lastly, from both a methodological and conceptual standpoint, amnestic MCI is typically viewed as a heterogeneous group, comprised of patients who will progress to dementia and those who will remain stable for several years or even revert back to normal cognition (Winblad et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies used neuropsychological measures of attention, memory and visuospatial abilities in which individuals aged from 60 to 80 years had their performance compared with individuals between 16 and 60 years of age 12 . Different tests have shown different rates of change between groups, being the memory test the first to show a significant decline 11 . In other tests, there was no evidence of significant change with increasing age [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Significant discrepancies occur in one or more test scores enabling the cognitive functioning assessment of psychiatric, educational or cultural impairment as is done in the patient's experiences, considering their historical circumstances 11,15,16 and emotional memories [17][18][19] . Several studies also suggest the effect of education level on the performance of cognitive tasks 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from the latter study indicated that older adults with MCI benefited from using semantic cues. Bennett, Golob, Parker, & Starr (2006) reported that older adults with MCI and normal controls (NC) did not differ in a measure of recall strategy (i.e., subjective organization and recall consistency), although MCI patients exhibited significantly lower performance in list recall. Froger, Taconnat, Landré, Beigneux, & Isingrini (2009), in a small but elegant study, reported that older adults with MCI used semantic cues during encoding, but performance benefits were observed only in tasks that used recognition paradigms.…”
Section: Introductionmentioning
confidence: 99%